THE EFFECT OF WEBBING ANGLE ORIENTATION ON PHYSICAL AND MECHANICAL PROPERTIES OF BOEHMERIA NIVEA FIBER COMPOSITES - Fajar Perdana Nurrullah; Fajar Paundra; Anas Maulana; Abdul Muhyi; Akhmad Nurdin; Indriyani Indriyani (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2023)
Composites are a combination of two or more different materials with different mechanical properties. The purpose of this research was to determine the effect of the angle orientation of the Boehmeria Nivea fiber-reinforced composite woven on the physical and mechanical properties. Boehmeria Nivea fiber is soaked in an alkaline solution and made into ropes with a diameter of 2-3 mm and then woven with angle orientations of 0o/15o, 0o/30o, 0o/45o and 0o/90o. The composite manufacturing process uses the press molding method. The tests in this study consisted of a tensile test with the ASTM D3039 standard, a flexural test with the ISO 178 standard and a density test with the ASTM C271 standard. Tensile test results show that the highest tensile strength occurs at 0°/15° webbing angle orientation, which is 13.77 Mpa. While the highest bending test results occur at the orientation of the 0°/15° webbing angle, which is 60.52 MPa. Tensile and flexural strength increases with smaller webbing angle orientation.